2015
DOI: 10.1158/0008-5472.can-14-3017
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cell-Penetrating Peptide-Based Vaccine Induces Robust CD4+ and CD8+ T Cell–Mediated Antitumor Immunity

Abstract: Vaccines that can coordinately induce multi-epitope T cellmediated immunity, T helper functions, and immunologic memory may offer effective tools for cancer immunotherapy. Here, we report the development of a new class of recombinant protein cancer vaccines that deliver different CD8 þ and CD4 þ T-cell epitopes presented by MHC class I and class II alleles, respectively. In these vaccines, the recombinant protein is fused with Z12, a novel cell-penetrating peptide that promotes efficient protein loading into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 46 publications
(45 reference statements)
0
44
0
Order By: Relevance
“…2). This was directly demonstrated using Zebra-derived CPPs, TAT, and penetratin [16, 22, 24, 46, 54, 55]. …”
Section: Multi-epitopic Antigenic Cargosmentioning
confidence: 99%
“…2). This was directly demonstrated using Zebra-derived CPPs, TAT, and penetratin [16, 22, 24, 46, 54, 55]. …”
Section: Multi-epitopic Antigenic Cargosmentioning
confidence: 99%
“…25 We previously showed that a fusion protein combining ZEBRA CPP with epitope peptides was able to promote CD8 and CD4 T cell responses and antitumor control. 10 In this report, we identified the most efficacious CPP truncationsadjuvants combinations to elicit simultaneous CD8 and CD4 T cell immune responses for both model-and TAA-antigens.…”
Section: Discussionmentioning
confidence: 97%
“…We demonstrated that a fusion protein combining ZEBRA CPP with a multiantigenic protein was able to deliver multiepitope peptides to DCs, and subsequently to promote cytotoxic T lymphocyte (CTL) and Th cell activation, and antitumor function. 10 Here, we have identified truncations of ZEBRA CPP with different structural characteristics that markedly improve antigenspecific CD8 and CD4 T cell immune responses both in vitro and in vivo. Responses were assessed not only to the model antigen ovalbumin (OVA), but also to the human melanoma/melanocyte proteins gp100 and MART-1, and to tyrosinase related protein 2(Trp2).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations